2002
DOI: 10.1034/j.1399-6576.2002.460821.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged apnea following succinylcholine administration in undiagnosed acute organophosphate poisoning

Abstract: Organophosphates (OP) are irreversibly bound to cholinesterase, causing deactivation of acetylcholinesterase. As a result of inhibition of plasma cholinesterase, increased sensitivity to drugs hydrolyzed by this enzyme can occur, e.g. succinylcholine and mivacurium. A case of more prolonged succinylcholine-induced paralysis in a child with undiagnosed acute OP insecticide poisoning is presented. A 7-h period of apnea and paralysis after administration of succinylcholine was attributed to the decreased rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…The use of a nondepolarizing neuromuscular blocker would be strongly recommended in this setting over succinylcholine, a depolarizing neuromuscular blocker. Because succinylcholine is metabolized by plasma cholinesterases, inhibition of these enzymes by nerve agents may lead to prolonged paralysis and untoward outcomes (Selden & Curry, 1987;Sener, Ustun, Kocamanoglu, & Tur, 2002 Institutions should develop computerized provider order entry order sets and electronic medication administration records for nerve agent exposure in advance. The emergent use of medications and dosages that are not routinely used in the ED provides for the perfect scenario for medication errors.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…The use of a nondepolarizing neuromuscular blocker would be strongly recommended in this setting over succinylcholine, a depolarizing neuromuscular blocker. Because succinylcholine is metabolized by plasma cholinesterases, inhibition of these enzymes by nerve agents may lead to prolonged paralysis and untoward outcomes (Selden & Curry, 1987;Sener, Ustun, Kocamanoglu, & Tur, 2002 Institutions should develop computerized provider order entry order sets and electronic medication administration records for nerve agent exposure in advance. The emergent use of medications and dosages that are not routinely used in the ED provides for the perfect scenario for medication errors.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…3 The duration of paralysis in most cases, however, was less than 4 hours. Similar prolongation of neuromuscular blockade has been reported for mivacurium, a nondepolarizing neuromuscular blocker (NMB) that is also metabolized by butyrylcholinesterase.…”
mentioning
confidence: 93%
“…Animal research suggests that a minimal plasma level of 4 µg/mL is effective in reversing nicotinic symptoms of poisoning; however, more recent research proposes that even higher levels may be necessary. 3,4 In either case, achieving and maintaining therapeutic plasma oxime levels varies depending on weight. In a randomized crossover study, healthy volunteers receiving pralidoxime as an initial bolus (4 mg/kg) followed up with a continuous infusion (3.2 mg/kg per hour) for 3.75 hours maintained mean therapeutic levels for more than 4 hours.…”
mentioning
confidence: 99%
“…Selden and Curry reported a case of prolonged succinylcholine-induced paralysis in a child with organophosphate insecticide poisoning (10). Ş ener et al reported a similar case of more prolonged succinylcholine-induced paralysis in a child with undiagnosed acute organophosphates insecticide poisoning (9). They noted that a 7-hour period of apnea and paralysis after administration of succinylcholine was attributed to the decreased rate of succinylcholine metabolism resulting from inhibition of pseudocholinesterase by the insecticide.…”
mentioning
confidence: 96%
“…For many OPs, the reaction is irreversible, and the signs and symptoms are prolonged over time, but more recent compounds are more readily and spontaneously dissociated. As a result of inhibition of plasma cholinesterase, increased sensitivity to drugs hydrolyzed by this enzyme can occur, e.g., succinylcholine and mivacurium (1,3,9). Selden and Curry reported a case of prolonged succinylcholine-induced paralysis in a child with organophosphate insecticide poisoning (10).…”
mentioning
confidence: 98%